Fetal microchimerism and maternal health during and after pregnancy - O'Donoghue, Keelin (Obstet Med, 2008)
Trafficking of fetal cells into the maternal circulation begins very early in pregnancy and the effects of this cell traffic are longlasting. All types of fetal cells, including stem cells, cross the placenta during normal pregnancy to enter maternal blood, from where they may be recovered in pregnancy for the purpose of genetic prenatal diagnosis. Fetal cells can also be located in maternal tissues during and after pregnancy, and persist as microchimeric cells for decades in marrow and other organs. Although persistent fetal cells were first implicated in autoimmune disease, subsequent reports routinely found microchimeric cells in healthy tissues and in non-autoimmune disease. Parallel studies in animal and human pregnancy now suggest instead that microchimeric fetal cells play a role in the response to tissue injury. However, it is still not clear whether microchimeric fetal cells persisting in the mother are an incidental finding, are naturally pathogenic or act as reparative stem cells, and the environmental or biological stimuli that determine microchimeric cell fate are as yet undetermined. Future studies must also focus on investigating whether fetal cells create functional improvement in response to maternal injury and whether this response can be manipulated. The pregnancy-acquired low-grade chimeric state of women could have far-reaching implications, influencing recovery after injury or surgery, ageing, graft survival after transplantation, survival after cancer as well as deciding the protective effect of pregnancy against diseases later in life. Lifelong persistence of fetal cells in maternal tissues may even explain why women live longer than men.